Immunogenicity of Low Dose Recombinant DNA Hepatitis B Vaccine in Children Ten Years Old and Younger - Wiharta A.S.; Purnawati S.P.; Zuraida Z.; Julfina B. (Indonesian Pediatric Society, 1997)
To evaluate the usefulness of low dose hepatitis-B vaccine, we recruited 70 healthy children of both sexes aged ten years or less. To be included in the study a child must have been clinically healthy and gave negative results for hepatitis-B virus infection (HBsAg, anti-HBs, anti-HBc), and with seerum glutamic oxaloacetic acid transaminase less than 50 mU/1. Subjects with intercurrent infection and those with chronic disease or moderate to severe malnutrition were excluded from the study. They were given 3 injections of 2,5 ml rDNA hepatitis B vaccine intramuscularly on month 0, month 1, and month 6. The seroconversion rate after the third injection in all subjects was 92.3%; this was slightly different between the well-nourished and under-nourished children (93.9% vs. 87,5%), and between girls and boys (96.7% vs 88.6%). The only side effect noted was fever encountered in 1 subject. We conclude that three intramuscular injections of 2.5 mg of rDNA hepatitis B vaccine give good anti-HBs titer, so that this method may be considered to be used in the mass immunization program.